Bridging Sustainability and Spirituality: Halal Eco-Tourism Practices in Indonesia - Kuat Ismanto; Hendri Hermawan Adinugraha; Moses Adeolu Agoi (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2026)
Objective: This research aims to examine the integration of halal ecotourism and sustainable tourism practices, and to explore how ecotourism grounded in Islamic ethical values contributes to environmental, economic, and socio-cultural sustainability. Method: This research employs a qualitative case-based approach. Researchers have conducted observations in tourist destinations and interviewed 10 informants. Data were analysed by analysing community-managed nature-based tourism destinations across mountainous, riverine, and coastal areas in Pekalongan Regency, Central Java, Indonesia. Result: The findings show that local communities manage most tourism destinations and implicitly apply halal principles, including environmental stewardship, provision of halal facilities, social ethics, and active community participation, which collectively reflect the three pillars of sustainable tourism and align with the maqasid al-shariah framework. Implication: This suggests that combining planning, implementation, and evaluation in a community-based halal eco-tourism framework can strengthen sustainable tourism development by integrating ecological conservation, local economic empowerment, and socio-cultural well-being. Originality or Novelty: This study offers a novel integrative model of halal eco-tourism as a value-driven approach to sustainable tourism, positioning it beyond a niche religious market and contributing to an alternative paradigm for future tourism development.